RESISTENSI KAYU PLASTIK TERHADAP TIGA JENIS JAMUR PERUSAK KAYU - Ginuk Sumarni; Jasni Jasni (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
Wood plastic composite samples made, from rubber wood (Hevea brasilliensis Muell. Arg.) were tested for durability againts Shizophyllum commune Fr, Pycnoporus sanguineus (Fr.) Karst and Dacryopinax spathularia (Schw.) Mart, fungi. The results shows that rubber wood plastic composite is not resistance againts the above three wood destroying fungus.